Romanian dentists' perception about direct restoration of dental caries on adjacent teeth: current techniques and materials, restorations longevity and failures. Part II - Irina-Maria Gheorghiu; Sebastian Onu; Alexandru Andrei Iliescu; Paula Perlea (Amaltea Medical Publishing House, 2024)
Proximal surfaces of both anterior and posterior teeth frequently present dental caries, as a result of complex coronal morphology and other associated factors which favors bacterial microfilm retention. In this article we present the second part results of a cross-sectional study, using a questionnaire that was distributed to a number of 110 Romanian dentists. We investigated the most used dental materials and techniques and correlations with oral restorations longevity, and also the failures and patients' complaints. The results indicate a modern, up to date approach of direct restoration in adjacent teeth from Romanian interviewed dentist.